Revolution of Bone and Teeth Health: Study of Aloe Barbadensis Instant Powder Formulation - Said, Fahmi; Rahmawati, Ida; Ningsih, Neny Setiawaty (JURNAL INFO KESEHATAN, 2023)
Aloe barbadensis is a plant with many applications such as anti-inflammatory, anti-fungal, anti-bacterial, and aiding in cell regeneration. Understanding aloe barbadensis' phytochemical profile and pharmacological action is essential since it is believed to have an impact on the formation of teeth and bones. The stability and bioavailability of Aloe barbadensis can be improved by formulating it as an instant powder. The research's objectives are to ascertain the Aloe barbadensis instant powder's qualitative and quantitative phytochemical profile, dosage formulations, and activity testing on hemoglobin, cholesterol, and red blood cell parameters. Samples of aloe barbadensis were washed, and they were then dried for 72 hours at 50°C. Following a maceration process using a 70% ethanol solvent, the extract was dried. Phytochemical screening, TLC profile, and extract description were employed to test the extract qualitatively. The quantities of total flavonoids, total anthraquinones, and total phenolics were determined to quantitatively test the extract. The formulation of the instant powder was then completed and evaluated on female mice using metrics associated with red blood cells, hemoglobin, and cholesterol levels. Furthermore, observations were made on the mice's liver organs. The study's findings revealed a qualitative profile of Aloe barbadensis extract, which included a tasteless, unique odor, milky white hue, and liquid shape. Aloe barbadensis has been demonstrated to contain flavonoids, phenolics, tannins, saponins, and anthraquinones, according to the results of phytochemical screening. Three spots, identified as Rf 3.2 and Rf 8.5 in the Rf 2.3 area, are visible in the chromatographic pattern. Total anthraquinones were discovered to be 4.59%, total flavonoids to be 0.24%, and total phenolic content to be 1.42%. The third formula of instant Aloe barbadensis pollen has been demonstrated through preclinical examinations to have the capacity to reduce cholesterol, boost hemoglobin, and enhance red blood cell count—all of which are associated with the growth of teeth and bones. An SPSS statistical study demonstrating statistically significant differences with other groups supports this. Mice liver histopathological examinations revealed no liver damage in any of the test groups.